PHARMACOVIGILANCE STUDY OF ANTICANCER DRUGS IN A DISTRICT GOVERNMENT HOSPITAL OF CENTRAL INDIA: A PROSPECTIVE OBSERVATIONAL STUDY - PATEL, ANERI; KUSHWAH, ANJALI (International Journal of Current Pharmaceutical Research, 2025)
Objective: Anticancer drugs are responsible for most adverse drug reactions (ADRs) in cancer patients worldwide. ADR reporting of anticancer drugs is sporadic in India, especially in rural areas, due to the lack of awareness and knowledge about the Pharmacovigilance Programme of India (PvPI). This study assessed the causality and severity pattern of ADRs with anticancer drugs in cancer patients. Methods: An observational, prospective, and single-center study was conducted at the oncology unit of the District Government Hospital, Jhabua, of Madhya Pradesh. Patients of either sex, aged>18 y, reporting ADRs with anticancer drugs from April 1, 2024, to July 31, 2024, were included. The analysis focused on demographic data of the patients, suspected drugs, causality assessment using the World Health Organization-Uppsala Monitoring Centre (WHO-UMC) scale, and severity assessment. Results: The age group of 41-60 y (61%) and females (68%) reported the highest number of ADRs. The maximum number of ADRs was reported with the use of platinum compounds (cisplatin, carboplatin, and oxaliplatin) (34%), followed by taxanes (paclitaxel and docetaxel) (28%). The gastrointestinal system (39.38%) was the most commonly involved, and nausea (20.33%) was the most common ADR among all. The majority of ADRs were certain (76%) and mild (48.36%). Conclusion: ADR reporting, monitoring, and timely management are important to increase the outcome of anticancer treatment. It’s important to increase awareness regarding PvPI among healthcare professionals and patients.